2018
DOI: 10.3171/2017.7.jns17380
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric changes and clinical outcome for petroclival meningiomas after primary treatment with Gamma Knife radiosurgery

Abstract: OBJECTIVE Petroclival meningiomas (PCMs) can cause devastating clinical symptoms due to mass effect on cranial nerves (CNs); thus, patients harboring these tumors need treatment. Many neurosurgeons advocate for microsurgery because removal of the tumor can provide relief or result in symptom disappearance. Gamma Knife radiosurgery (GKRS) is often an alternative for surgery because it can cause tumor shrinkage with improvement of symptoms. This study evaluates qualitative volumetric changes of PCM after primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
(104 reference statements)
2
7
0
Order By: Relevance
“…In addition, when the tumor presented with a large volume and wide extension into the multi-cranial fossa, they were concerned about a higher failure rate of GKRS. Furthermore, there are not many studies on the outcomes of GKRS for PCMs [ 3 4 5 6 7 8 21 22 ] ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when the tumor presented with a large volume and wide extension into the multi-cranial fossa, they were concerned about a higher failure rate of GKRS. Furthermore, there are not many studies on the outcomes of GKRS for PCMs [ 3 4 5 6 7 8 21 22 ] ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Gamma Knife radiosurgery (GKRS) can be conducted as an initial alternative treatment for PCM, as in skull base meningiomas. Although the effectiveness of adjuvant or alternative GKRS for PCM has already been demonstrated in several studies [ 3 4 5 6 7 8 ], the precise treatment guidelines have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they also observed that female patients were more likely to have a favorable outcome after GKRS, confirming that gender is an element that merits consideration in decisionmaking process. Sadik et al [123] recently described the results of RS in 60 patients with small, incidental PCMs with a mean tumor volume of 4.00 cm 3 (range 0.13-11.35 cm 3 ). Local tumor control was 98% at 5 years and 93% at 7 years.…”
Section: Trigeminal Neuralgia Is Indeed Common In Patients Withmentioning
confidence: 99%
“…From 2 to 12% of patients with posterior fossa tumors such as petroclival meningiomas (PCMs) can present with TN by direct compression of the trigeminal nerve root as it enters the brain stem, regardless of tumor size [5,8,20,29,35]. Current treatment options for tumor-induced TN include glycerol rhizotomy, radiofrequency ablation, percutaneous balloon microcompression, gamma knife radiosurgery (GKRS), and microsurgery (MS) when medication alone is insufficient [4,6,10,12,17,18,21,26,33,36]. Direct removal of mass effect by MS seems to be the most logical and effective method to achieve pain control [8,10,18,21], but there is a debate since PCMs have a deep-seated location within the skull base with multitude of critical neurovascular structures surrounding the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…reasons, the role of GKRS for small PCMs has gained increasing acceptance over the past decade for its acceptable tumor control and minimal morbidity rates [13,18,21,27,33]. However, there are so far no articles in literature defining the role of MS compared to GKRS for newly diagnosed, small PCMs on TN relief without medications.…”
Section: Introductionmentioning
confidence: 99%